2g-m=5-gh

Simple and best practice solution for 2g-m=5-gh equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2g-m=5-gh equation:


Simplifying
2g + -1m = 5 + -1gh

Solving
2g + -1m = 5 + -1gh

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add 'gh' to each side of the equation.
2g + gh + -1m = 5 + -1gh + gh

Combine like terms: -1gh + gh = 0
2g + gh + -1m = 5 + 0
2g + gh + -1m = 5

Add 'm' to each side of the equation.
2g + gh + -1m + m = 5 + m

Combine like terms: -1m + m = 0
2g + gh + 0 = 5 + m
2g + gh = 5 + m

Reorder the terms:
-5 + 2g + gh + -1m = 5 + m + -5 + -1m

Reorder the terms:
-5 + 2g + gh + -1m = 5 + -5 + m + -1m

Combine like terms: 5 + -5 = 0
-5 + 2g + gh + -1m = 0 + m + -1m
-5 + 2g + gh + -1m = m + -1m

Combine like terms: m + -1m = 0
-5 + 2g + gh + -1m = 0

The solution to this equation could not be determined.

See similar equations:

| 4x^3=5.5 | | 4x+5-7=26 | | -(8x+8)=-72 | | -2(6x-5)=46 | | 4x^2+5x+6=0 | | 9y^2+19=30y | | -x^2-198=0 | | 27p^3-108pq^3=0 | | x^2+18+76=0 | | -19=8-3(-2k-3) | | x+y=1300 | | 3(1-x)=24 | | -16h=8(2h-10) | | 6a^2-6=0 | | 6b=-42-b | | 0=a^2+12a+32 | | 2m^3=7 | | 3x-(5x-3)=26 | | ln(x-2)-ln(x+3)=ln(x-1)-ln(x+7) | | -7(a-8)=7 | | 7s^2-19st+10t^2=0 | | 12x^5-11x^7+15x^8=0 | | 9x-7y=8 | | 6q=24q+6 | | x+(x+6)=4 | | 41-q=3q-15 | | 5-2p=6*q+1 | | 28+y=90 | | f(-11.9)=[-11.9+.5]-3 | | 25+2t=5t+10 | | -15=x-35 | | -16t^2+32t+768=528 |

Equations solver categories